2009
DOI: 10.5138/ijpm.2009.0975.0185.05791
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carum carvi and Curcuma longa on hormonal and reproductive parameter of female rats.

Abstract: Background: Rhizome of Curcuma longa and seeds of Carum Carvi a folk medicinal plant used as have antifertility potentials. Present investigation study the effect of both the plant on hormone and reproductive parameter of female rat. The aqueous and ethanolic extract of rhizome of Curcuma longa and seeds of Carum Carvi used for testing antifertility activity in female rat. Aqueous and ethanolic extract of plants were administered orally to female rat for 30 consecutive days. Estrous cycle, reproductive hormone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 12 publications
4
13
0
1
Order By: Relevance
“…Artemisia herba-alba, on the other hand, causes a significant decrease in the relative ovarian weights and embryo weights in rats in addition to reductions in percentage pregnancies and in the number of implantation sites and viable fetus number Qazan et al 2007, Priya et al 2014. Carum carvi and Trigonella foenum-graecum L. (Fabaceae) exert their antifertility effect by significant reduction of Leutinzing Hormone (LH) and Follicle Stimulating Hormone (FSH), blockage of estrus phase with increase in weights of ovaries, uterus and body (Thakur et al 2009;Agrahari & Singh 2014;Priya et al 2014). Accordingly, pregnant women or those who would like to conceive should be discouraged from the consumption of these herbs.…”
Section: Herbal Remedies With Female Antifertility and Abortificiant mentioning
confidence: 99%
See 1 more Smart Citation
“…Artemisia herba-alba, on the other hand, causes a significant decrease in the relative ovarian weights and embryo weights in rats in addition to reductions in percentage pregnancies and in the number of implantation sites and viable fetus number Qazan et al 2007, Priya et al 2014. Carum carvi and Trigonella foenum-graecum L. (Fabaceae) exert their antifertility effect by significant reduction of Leutinzing Hormone (LH) and Follicle Stimulating Hormone (FSH), blockage of estrus phase with increase in weights of ovaries, uterus and body (Thakur et al 2009;Agrahari & Singh 2014;Priya et al 2014). Accordingly, pregnant women or those who would like to conceive should be discouraged from the consumption of these herbs.…”
Section: Herbal Remedies With Female Antifertility and Abortificiant mentioning
confidence: 99%
“…Significant antifertility in female rats for significant reductions in LH and FSH, blockage of estrus phase with increase in weights of ovaries, uterus and body (Thakur et al 2009;Priya et al 2014;Agrahari & Singh 2014). Caraway is considered among herbs commonly associated with galactogogue properties, but strongly contraindicated in pregnancy and breastfeeding due to its antispasmodic effects (Mannion & Mansell 2012).…”
Section: Introductionmentioning
confidence: 99%
“…One of the free radicals is the Reactive Oxygen Species (ROS) group [10]. ROS can cause lipid peroxidation, a chain reaction that will produce MDA, inhibition of the free radical activity of ROS group by curcumin will inhibit also lipid peroxidation process and cause decreasing MDA production [22].…”
Section: Resultsmentioning
confidence: 99%
“…Thakur et al [16] reported that both aqueous and ethanolic extracts of rhizome of Curcuma longa showed a significant antifertility activity in female albino rats. Also the amount of estrogen in ethanolic extract treated animals was found to have increased significantly.…”
Section: Resultsmentioning
confidence: 99%